2022
DOI: 10.1186/s12967-022-03480-x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking TIGIT/CD155 signalling reverses CD8+ T cell exhaustion and enhances the antitumor activity in cervical cancer

Abstract: Objective TIGIT/CD155 has attracted widespread attention as a new immune checkpoint and a potential target for cancer immunotherapy. In our study, we evaluated the role of TIGIT/CD155 checkpoints in the progression of cervical cancer. Methods The expression of CD155 and TIGIT in cervical cancer tissues was detected using flow cytometry, immunohistochemistry (IHC) and gene expression profiling. In vivo and in vitro experiments have proven that block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…These transcription factors include: ILF3, RFXANK, RFXAP, RFX5, CIITA, RELA, NFKB1, AR, E2F1, STAT3 and JUN. Consistent with the conclusions of other studies, NFKB1/RelA heterodimers participated in NF-kB signaling pathway activation, which is an important factor for Tex production (35)(36)(37). Transcription factors CIITA, RFX5, RFXAP, and RFXANK mutations have been associated with Major histocompatibility complex (MHC) II deficiency, so they're also associated with immune exhaustion.…”
Section: Discussionsupporting
confidence: 89%
“…These transcription factors include: ILF3, RFXANK, RFXAP, RFX5, CIITA, RELA, NFKB1, AR, E2F1, STAT3 and JUN. Consistent with the conclusions of other studies, NFKB1/RelA heterodimers participated in NF-kB signaling pathway activation, which is an important factor for Tex production (35)(36)(37). Transcription factors CIITA, RFX5, RFXAP, and RFXANK mutations have been associated with Major histocompatibility complex (MHC) II deficiency, so they're also associated with immune exhaustion.…”
Section: Discussionsupporting
confidence: 89%
“…Although altered expression profiles of DNAM-1, CRTAM, Tactile and TIGIT are reported in peripheral blood samples of patients diagnosed with MS, RA, SSc, psoriasis, etc., a correlation with disease severity and progression in time is often lacking. In addition, modulating the DNAM-1/TIGIT axis is highly investigated as a therapeutic target in oncoimmunity, and can also be of interest to target autoimmunity to boost immunoregulation and reduce target-cell killing [ 104 , 105 ]. Furthermore, genetic variants of DNAM-1 [ 22 ], CRTAM [ 72 ] and Tactile [ 94 ] are identified as being related to autoimmune susceptibility, the hub gene for diagnosis and unresponsiveness to immunosuppressive therapies, which underscores the importance of further genome-wide association studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, TIGIT triggering by Necl-5 + target cells results in the disruption of granule polarization through the recruitment of SHIP1 by its ITT-like motif [ 3 , 9 , 103 ]. Similarly, SHIP1 recruitment to TIGIT on CD8 + CTLs results in reduced secretion of granzyme B, TNF-α and IFN-γ due to inhibition of ERK, MAPK and transcription factor NF-κB [ 104 ]. Blockage of the TIGIT–Necl-5 interaction restores the impaired NK cell and CD8 + CTL effector function.…”
Section: Effector Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, by interacting with three ligands (CD155, CD112, and CD113) expressed on the surface of tumor cells, TIGIT causes the immune system to be suppressed ( 120 ). In this regard, Liu et al., in 2022, demonstrated that TIGIT is a novel therapeutic target in cervical malignancy; additionally, it plays a significant role in preclinical models of cervical cancer following inhibition of TIGIT by monoclonal antibodies, both alone and in combination with anti-PD-1/PD-L1 antibodies ( 121 ). On the other hand, similar to PD-1/PD-L1, TIGIT plays a role in inhibiting the tumor immune system and both are upregulated in different types of malignancies ( 119 ).…”
Section: Functions Of Monoclonal Antibodies Against Cervical Cancermentioning
confidence: 99%